Capturing Context-Sensitive Information Usage in Choice Models via Mixtures of Information Archetypes. (October 2016) - Swait, Joffre; Popa, Monica; Wang, Luming
The authors offer a new conceptualization and operational model of consumer choice that allows context-sensitive information usage and preference heterogeneity to be separately and simultaneously captured, thus transforming the axiom of full information use into a testable hypothesis. A key contribution of the proposed framework is the integration of two previously disjointed and often antagonistic research paradigms: (1) the economic rationality perspective, which assumes stable preferences and full information usage, and (2) the psychological bounded-rationality perspective, which allows context-sensitive preferences and information selectivity. The authors demonstrate that the two paradigms can and do coexist in the same decision-making space, even at the level of individual consumer choices. The proposed information archetype mixture model is tested in four studies that span different product categories and levels of task complexity. The findings have ramifications for choice modeling theory and implementation, beyond the disciplinary boundaries of marketing to applied economics and choice-focused social sciences.